CoFe2O4-filled carbon nanotubes as anode material for lithium-ion batteries - Moeller, Lucas; Thauer, Elisa; Ottmann, Alexander; Deeg, Lukas; Ghunaim, Rasha; Hampel, Silke; Klingeler, Rüdiger (Journal of alloys and compounds, 2020)
Nanosized particles of cobalt ferrite CoFe2O4 incorporated into multi-walled carbon nanotubes (CNT) have been studied as anode material for Li-ion batteries. In order to evaluate the benefits of CNT shells, the results are compared to bare CoFe2O4 nanoparticles. Electrochemical measurements by means of cyclic voltammetry and galvanostatic cycling show typical redox activity associated with the ferrite conversion reaction which implies that the filled nanomaterial is electrochemically active. Galvanostatic cycling measurements reveal better cycling stability of the CNT-incorporated compared to the bare ferrite nanoparticles. The data imply that embedding nanoparticles inside the protective and conductive shells of CNTs opens a way to utilize high theoretical capacities of CoFe2O4 for electrochemical energy storage.
Im Titel sind die Zahlen "2" und "4" in CoFe2O4 tiefgestellt
Gesehen am 23.06.2020